High-crystallinity copolyester based on furandicarboxylic acid as well as preparation method and application of high-crystallinity copolyester
By using furandicarboxylic acid and specific aliphatic diols in high-crystalline copolyesters, combined with esterification and melt polycondensation processes, the problem of poor performance under existing high temperature conditions was solved, and the development of high heat resistance and high crystalline bio-based materials was achieved.
Patent Information
- Application Number
- CN202411524189.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing high-crystalline copolyester materials have poor performance under high temperature conditions and are mostly derived from petroleum-based monomers, making it difficult to develop high-heat resistance and high-crystalline bio-based engineering plastics.
Copolyesters with excellent crystallization properties and high heat resistance temperatures are prepared by using high crystallization copolyesters based on furandicarboxylic acid through specific raw material ratios and processes, including esterification reaction and melt polycondensation.
The glass transition temperature, melting point and heat resistance temperature of high crystalline copolyester are significantly improved, ensuring that it maintains good performance at higher temperatures, and the development of bio-based materials is realized, solving the problems of insufficient heat resistance and gas barrier properties of traditional plastics.
Smart Images

Figure CN119505201A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, in particular to a high-crystalline copolyester and a preparation method and products thereof, and specifically to a high-crystalline copolyester based on furandicarboxylic acid with high crystallinity and high glass transition temperature and a preparation method thereof, as well as application in the preparation of products. Background Art
[0002] At present, the common high-crystalline materials on the market are mainly polyester polymers, including polybutylene succinate (PBS), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), poly-1,4-cyclohexanedimethanol terephthalate (PCT), etc. Among them, PBS is an aliphatic polyester with a heat resistance temperature of about 100°C, and its application is limited under high temperature conditions; PET has good mechanical properties, but its heat resistance is general, and its heat resistance temperature is around the glass transition temperature, which cannot meet the use temperature resistance requirements above 100°C; PBT has excellent crystallization ability, but its glass transition temperature is low, and its heat resistance temperature fluctuates greatly due to the influence of crystallinity; PCT has a melting point close to 300°C and is easy to decompose during the polymerization and processing process. In general, the above copolyesters have certain limitations, and they are all derived from petroleum-based monomers. At present, the development and application of high-heat-resistant and high-crystalline bio-based engineering plastics still face severe challenges.
[0003] At present, the modification methods of high heat-resistant copolyester materials mainly include physical blending and chemical modification. Among them, the chemical copolymerization method starts from the source of the material and is expected to obtain a new high heat-resistant and high crystallinity copolyester structure. Bio-based 2,5-furandicarboxylic acid is a new type of aromatic dibasic acid. The poly 2,5-furandicarboxylic acid 1,4-cyclohexanedimethanol (PCF) obtained based on 2,5-furandicarboxylic acid and 1,4-cyclohexanedimethanol has a melting point that is 20-30°C lower than that of PCT, but maintains a high glass transition temperature and crystallization ability. It is a new type of high crystallinity and high heat-resistant copolyester. However, due to the asymmetry of 2,5-furandicarboxylic acid, as well as the high segment rigidity and high structural steric hindrance of PCF, the half-crystallization time is still relatively long. For example, at 170°C, the half-crystallization time of PCF68 is 73s. Summary of the invention
[0004] The main purpose of the present invention is to provide a high-crystalline copolyester based on furandicarboxylic acid and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0005] Another object of the present invention is to provide the application of the highly crystalline copolyester based on furandicarboxylic acid.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] The embodiment of the present invention provides a high crystalline copolyester based on furandicarboxylic acid, the structural formula of which is shown in the following formula (1):
[0008]
[0009] Wherein, R1 is -O(CH2) a O-, R2 is -O(CH2) b O-, a, b, x, y, z, n are all integers, a=2~6, b=6~12, x=1~10, y=1~10, z=1~10, n=20~100; and, (x+z)∶y=1∶1~1∶10.
[0010] The embodiment of the present invention also provides a high crystalline copolyester based on furandicarboxylic acid, which is prepared from raw materials including the following components:
[0011] 2,5-Furandicarboxylic acid and / or 2,5-furandicarboxylic acid esters;
[0012] A 1,4-cyclohexanedimethanol composition, comprising trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%;
[0013] A first aliphatic diol having 2 to 6 carbon atoms;
[0014] The second aliphatic diol having 6 to 12 carbon atoms.
[0015] The embodiment of the present invention also provides a method for preparing a highly crystalline copolyester based on furandicarboxylic acid, which comprises:
[0016] Conducting an esterification reaction or an esterification reaction on a first mixed reaction system comprising 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, a 1,4-cyclohexanedimethanol composition, a first aliphatic diol having 2 to 6 carbon atoms, a second aliphatic diol having 6 to 12 carbon atoms, and an esterification catalyst to obtain a copolyester oligomer, wherein the 1,4-cyclohexanedimethanol composition comprises trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%;
[0017] Under vacuum conditions, a second mixed reaction system comprising the copolyester oligomer and a polycondensation catalyst is subjected to a melt polycondensation reaction to prepare a furandicarboxylic acid-based high-crystalline copolyester.
[0018] The embodiment of the present invention also provides the use of the above-mentioned furandicarboxylic acid-based high-crystalline copolyester in the fields of preparing packaging materials, heat-resistant materials, agricultural mulch films, cling films or food tableware.
[0019] Correspondingly, an embodiment of the present invention further provides a high crystalline copolyester product, which is prepared from the above-mentioned high crystalline copolyester based on furandicarboxylic acid.
[0020] Compared with the prior art, the beneficial effects of the present invention include:
[0021] 1) The high crystalline copolyester based on furandicarboxylic acid provided by the present invention has excellent crystallization performance and rapid crystallization ability. Compared with amorphous copolyester, due to the presence of high trans-high content 1,4-cyclohexanedimethanol and its inner ring structure, the glass transition temperature, melting point and heat resistance temperature of the high crystalline copolyester as a whole are significantly improved, so that it can maintain good overall performance even at a higher use temperature;
[0022] 2) In the preparation of the high-crystalline copolyester of the present invention, due to the presence of short-chain aliphatic diols, the short-chain aliphatic diols are removed during the polycondensation process, so that the reaction proceeds in the forward direction, and the molecular weight increases rapidly, thereby obtaining a high-molecular-weight and high-performance copolyester; the presence of long-chain flexible aliphatic diols can effectively improve the crystallization ability of the copolyester and optimize the toughness of the copolyester due to the easy-to-turn flexibility of the long aliphatic chains;
[0023] 3) The present invention, through the introduction of two aliphatic diols, can not only appropriately reduce the melting point to 220-270°C, but also appropriately improve the crystallization ability of the copolyester and significantly improve the polymerization efficiency, thereby obtaining a copolyester with higher intrinsic viscosity, higher molecular weight, lower acid value and hydroxyl value than PCF polyester. It is expected to obtain bio-based high-crystalline engineering plastics with better comprehensive performance, which can be widely used in high temperature resistant materials, express packaging, food packaging, food tableware and other fields, effectively solving the problems of plastics being not heat-resistant and having poor gas barrier properties, and realizing the effective utilization of high-crystalline materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The NMR of the highly crystalline copolyester prepared in Example 1 of the present invention is 1 H-NMR spectrum;
[0026] Figure 2 is a secondary temperature rise DSC graph of the highly crystalline copolyester prepared in Example 1 of the present invention;
[0027] Figure 3 is a stress-strain diagram of the highly crystalline copolyester prepared in Example 1 of the present invention;
[0028] Figure 4 is a graph of relative crystallinity and crystallization time of the highly crystalline copolyester prepared in Example 1 of the present invention;
[0029] Figure 5 is a GPC curve diagram of the highly crystalline copolyester prepared in Example 1 of the present invention;
[0030] Figure 6 It is the TGA chart of the highly crystalline copolyester prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In view of the current synthesis status of highly crystalline heat-resistant copolyesters, the inventors of this case proposed a highly crystalline copolyester and a preparation method thereof after long-term research and a large number of experiments. The copolyester is mainly based on the PCF structure, and the content of 1,4-cyclohexanedimethanol in the copolyester is precisely adjusted, the content of diols with stronger crystallization ability of the chain segments is controlled, and a small amount of flexible aliphatic diols is introduced. It is expected that the crystallization rate of the copolyester will be further improved on the basis of retaining the high crystallization ability of the PCF chain segments, and the toughness of PCF will be improved or the heat resistance will be further enhanced, so as to obtain a new type of highly crystalline bio-based copolyester.
[0032] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0034] As one aspect of the technical solution of the present invention, the structure of a high crystalline copolyester based on furandicarboxylic acid is shown in the following formula (1):
[0035]
[0036] Wherein, R1 is -O(CH2) a O-, R2 is -O(CH2) bO-, a, b, x, y, z, n are all integers, a=2~6, b=6~12, x=1~10, y=1~10, z=1~10, n=20~100; and, (x+z)∶y=1∶1N1∶10.
[0037] In some embodiments, the glass transition temperature of the high crystalline copolyester is 76-87°C, the melting temperature is 230-270°C, and the half crystallization time of the high crystalline copolyester during isothermal crystallization in the range of 160-200°C is 18-90s.
[0038] In some embodiments, the high crystalline copolyester has an intrinsic viscosity of 0.7 dL / g to 1.3 dL / g, a number average molecular weight of 30,000 g / mol to 70,000 g / mol, a molecular weight distribution of 1.6 to 2.0, an acid value of 20 to 40 mol / t, and a hydroxyl value of 30 to 50 mgKOH / g.
[0039] In summary, the high crystalline copolyester based on furandicarboxylic acid provided by the present invention not only has good crystallization properties, but also has excellent thermodynamic properties and mechanical properties.
[0040] As another aspect of the technical solution of the present invention, a high crystalline copolyester based on furandicarboxylic acid is prepared from raw materials including the following components:
[0041] A first monomer, namely 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester;
[0042] The second monomer, i.e., a 1,4-cyclohexanedimethanol composition, comprises trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%, and the content of cis-1,4-cyclohexanedimethanol is 22% to 25% accordingly;
[0043] The third monomer is a first aliphatic diol having 2 to 6 carbon atoms;
[0044] The fourth monomer is a second aliphatic diol having 6 to 12 carbon atoms.
[0045] In some embodiments, the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%. The high-crystalline copolyester of the present invention has excellent crystallization performance and rapid crystallization ability. Compared with amorphous copolyesters, due to the presence of high-trans and high-content 1,4-cyclohexanedimethanol, thanks to its inner ring structure, the glass transition temperature, melting point and heat-resistant temperature of the high-crystalline copolyester as a whole are significantly improved, so that it can maintain good overall performance at a higher use temperature.
[0046] Furthermore, the present invention effectively controls the molar content of the 1,4-cyclohexanedimethanol composition in the copolyester diol to be between 60% and 90%. In other words, in the mixture of the 1,4-cyclohexanedimethanol composition, the first aliphatic diol, and the second aliphatic diol, the molar content of the 1,4-cyclohexanedimethanol composition is 60N90%.
[0047] In some embodiments, in the mixture of 1,4-cyclohexanedimethanol composition, first aliphatic diol and second aliphatic diol, the molar content of the third monomer first aliphatic diol is 5N35%, and the molar content of the fourth monomer second aliphatic diol is 5-10%.
[0048] In some embodiments, the molar ratio of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, 1,4-cyclohexanedimethanol composition, the first aliphatic diol and the second aliphatic diol is 1:0.6:0.35:0.05 to 1:0.9:0.05:0.05.
[0049] In some embodiments, the third monomer first aliphatic diol used in the present invention can include any one or a combination of two or more of ethylene glycol, 1,2-pentanediol, 1,4-pentanediol, 1,5-pentanediol, neopentyl glycol, 3-methyl 1,5-pentanediol, diethylene glycol, 1,6-hexanediol, etc., preferably ethylene glycol. The removal of the third monomer during the polycondensation process promotes molecular weight growth.
[0050] In some embodiments, the fourth monomer second aliphatic diol used in the present invention may include any one or a combination of two or more of 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dihydroxydodecane, etc., preferably octanediol. Due to its long chain flexibility, the fourth monomer can improve the overall crystallization ability and improve the toughness, and finally obtain a high crystalline copolyester with excellent thermal properties, excellent mechanical properties and good crystallization properties.
[0051] In summary, due to the presence of the second diol (i.e., the first aliphatic diol having 2 to 6 carbon atoms), the present invention is removed during the polycondensation process, so that the reaction proceeds in the forward direction, the molecular weight increases rapidly, and a high-molecular-weight and high-performance copolyester is obtained; the presence of the third diol (i.e., the second aliphatic diol having 6 to 12 carbon atoms) can effectively improve the crystallization ability of the copolyester and optimize the toughness of the copolyester due to the easy-to-flip flexibility of the long fatty chain.
[0052] As another aspect of the technical solution of the present invention, a method for preparing a highly crystalline copolyester based on furandicarboxylic acid comprises:
[0053] Conducting an esterification reaction or an esterification reaction on a first mixed reaction system comprising 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, a 1,4-cyclohexanedimethanol composition, a first aliphatic diol having 2 to 6 carbon atoms, a second aliphatic diol having 6 to 12 carbon atoms and an esterification catalyst to obtain a copolyester oligomer, wherein the 1,4-cyclohexanedimethanol composition comprises trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%;
[0054] Under vacuum conditions, a second mixed reaction system comprising the copolyester oligomer and a polycondensation catalyst is subjected to a melt polycondensation reaction to prepare a furandicarboxylic acid-based high-crystalline copolyester.
[0055] In some embodiments, in the above preparation method, the molar ratio of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, 1,4-cyclohexanedimethanol composition, the first aliphatic diol and the second aliphatic diol is 1:0.6:0.35:0.05N1:0.9:0.05:0.05.
[0056] In order to further coordinate the structural units of the highly crystalline copolyester, the present invention adopts a diol unit with stronger segment crystallization ability, thereby improving the overall crystallization ability of the copolyester and better adjusting the comprehensive properties of the copolyester such as heat resistance, crystallization, and mechanical properties. The structural unit of the second diol is selected from the structural unit of the first aliphatic diol having 2 to 6 carbon atoms. Specifically, the type of the first aliphatic diol is as defined above and will not be repeated here.
[0057] In order to further coordinate the structural units of the highly crystalline copolyester, a diol unit with a longer chain segment and better flexibility is used, thereby improving the overall crystallization ability of the copolyester and improving the toughness of the copolyester, the structural unit of the third diol is selected from the structural unit of the second aliphatic diol having a carbon number of 6 to 12. Specifically, the type of the second aliphatic diol is as defined above and will not be repeated here.
[0058] Therefore, the present invention can reasonably select the structural unit containing diol according to the needs of different molecular structures to obtain high crystalline copolyesters with different structural formulas.
[0059] The preparation mechanism of the high crystalline copolyester of the present invention is: 2,5-furandicarboxylic acid or its ester, high trans 1,4-cyclohexanedimethanol, a third monomer and a fourth monomer aliphatic diol are melt-polycondensed, and the high proportion of 1,4-cyclohexanedimethanol with a high trans content (75-78%) in the copolyester is accurately controlled by controlling the polymerization conditions and using a catalyst, and the third monomer (preferably ethylene glycol) is removed during the polycondensation process to promote the molecular weight growth and the flexibility brought by the long chain of the fourth monomer diol, so as to obtain a high molecular weight, low acid value, and low hydroxyl value high crystalline copolyester.
[0060] The present invention also gives the highly crystalline copolyester excellent gas barrier properties. When 2,5-furandicarboxylic acid and its esters and 1,4-cyclohexanedimethanol are used for polymerization, the steric hindrance of the highly crystalline copolyester molecular chain is further increased, so that the diffusion path of small gas molecules such as CO2, O2, and N2 is further reduced, thereby further improving the gas barrier performance of the highly crystalline copolyester, which has obvious advantages over industrially produced PET on the market in various gas barrier aspects.
[0061] Poly (2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol) (PCF) has a melting point of more than 270°C, and thus requires a polycondensation temperature of more than 290°C, which places too high demands on polymerization equipment and reactors, and thus cannot be prepared on a large scale. The present invention introduces the third and fourth monomers, aliphatic diols, which not only can appropriately lower the melting point to 220-270°C, but also can appropriately improve the crystallization ability of the copolyester and significantly improve the polymerization efficiency, thereby obtaining a copolyester with a higher intrinsic viscosity, a higher molecular weight, and a lower acid value and hydroxyl value than PCF polyester, and is expected to obtain a bio-based high-crystalline engineering plastic with better comprehensive performance.
[0062] In some embodiments, the preparation method of the highly crystalline copolyester comprises: subjecting the first mixed reaction system to an esterification reaction or an ester exchange reaction at 170 to 220° C. for 4 to 6 hours; when the yield of byproduct water or methanol reaches 95% or more, the esterification reaction or the ester exchange reaction is completed to obtain a first intermediate product;
[0063] In some embodiments, the esterification catalyst used to prepare the highly crystalline copolyester must include any one or a combination of two or more of a titanium-based catalyst, an antimony-based catalyst, a tin-based catalyst, a germanium-based catalyst, etc., preferably including at least one of tetrabutyl titanate, isopropyl titanate, and antimony acetate.
[0064] In some embodiments, the molar amount of the esterification catalyst is 1‰ to 3‰ of the total molar amount of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0065] In some embodiments, the preparation method of the highly crystalline copolyester includes: first maintaining the second mixed reaction system in a low vacuum state, then increasing the vacuum degree until the melt polycondensation reaction is stable, maintaining the vacuum degree below 7 Pa, and restoring normal pressure after the reaction is completed to obtain a highly crystalline copolyester based on furandicarboxylic acid.
[0066] In some embodiments, the temperature of the melt polycondensation reaction is 250° C. to 270° C., and the time of the melt polycondensation reaction is 5 h to 10 h.
[0067] In some embodiments, in the step of melt polycondensation reaction, the vacuum degree is less than or equal to 7Pa.
[0068] In some embodiments, the polycondensation catalyst comprises a mixture of an antimony-based catalyst and a titanium-based catalyst. Further, the mass ratio of the antimony-based catalyst to the titanium-based catalyst is 5:5 to 9:1.
[0069] The antimony catalyst may include at least one of antimony trioxide, antimony acetate, antimony glycol, etc., but not limited thereto. The titanium catalyst may include at least one of tetrabutyl titanate, titanium dioxide, potassium hexafluorotitanate, etc., but not limited thereto.
[0070] In some more preferred embodiments, the polycondensation catalyst includes a mixture of antimony trioxide and tetrabutyl titanate.
[0071] In some embodiments, the molar amount of the polycondensation catalyst is 1‰ to 3‰ of the total molar amount of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0072] In some embodiments, in the melt polycondensation step, the second mixed reaction system further includes at least any one of a stabilizer, an antioxidant, and the like.
[0073] In some embodiments, the molar amount of the stabilizer is 1‰ to 5‰ of the total molar amount of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0074] In some embodiments, the stabilizer is selected from phosphorus-based stabilizers, wherein the phosphorus-based stabilizer may include at least any one of phosphorous acid, diphenyl phosphate, triphenyl phosphate, triphenyl phosphite, etc., preferably includes at least any one of triphenyl phosphate, triphenyl phosphite, etc., but is not limited thereto.
[0075] In some embodiments, the molar amount of the antioxidant is 0.4‰ to 0.6‰ of the total molar amount of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0076] In some embodiments, the antioxidant is selected from phenolic antioxidants, wherein the phenolic antioxidant may include at least any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), etc., preferably includes at least any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc., but is not limited thereto.
[0077] In some more specific preferred embodiments, the method for preparing the highly crystalline copolyester based on furandicarboxylic acid comprises the following steps:
[0078] Step 1: 2,5-furandicarboxylic acid or its esterified product, 1,4-cyclohexanedimethanol composition, two diols (i.e., a first aliphatic diol, a second aliphatic diol) and an esterification catalyst are mixed to form a system, and the mixed system is subjected to an esterification reaction or an ester exchange reaction at 170-220° C. until the yield of byproduct water or methanol is at least 95%, thereby obtaining a copolyester oligomer;
[0079] Step 2: Add various polycondensation aids (i.e., polycondensation catalysts, stabilizers, antioxidants, etc.) to the copolyester oligomers obtained in step 1. The reaction system is first maintained in a low vacuum state for 0.5 hours to prevent the oligomers from splashing and being drawn out, thereby blocking the pipeline and causing ratio deviation. The polycondensation temperature is set according to different monomer ratios. After maintaining the low vacuum state for a period of time, the vacuum degree of the system is slowly increased until the stable vacuum degree of the polycondensation reaction is less than or equal to 7Pa. The polycondensation time is 5 to 10 hours, and then nitrogen is introduced to restore normal pressure to obtain a high molecular weight and high crystalline copolyester product.
[0080] The present invention accurately controls the content of high trans 1,4-cyclohexanedimethanol in the copolyester according to the set polymerization conditions and the catalyst used, and obtains a high molecular weight, low acid value, and low hydroxyl value high crystalline copolyester. Due to the presence of high trans high content 1,4-cyclohexanedimethanol, thanks to the regularity of its trans structure, a high molecular weight copolyester is obtained, so that the copolyester has not only good crystallinity but also good mechanical properties.
[0081] Furthermore, in step 2, the molar amount of the polycondensation catalyst is 1‰ to 3‰ of the total molar amount of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0082] Furthermore, the molar amount of the stabilizer is 1‰ to 5‰ of the total molar amount of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester.
[0083] Furthermore, the polycondensation reaction in step 2 can avoid the common problem of copolyester polymerization component deviation according to the control of the polycondensation temperature and the polycondensation method, so as to achieve precise control of the composition of the copolyester and thus achieve the effect of regulating thermal properties.
[0084] The preparation method of the above-mentioned high-crystalline copolyester of the present invention comprises the following steps: synthesizing 2,5-furandicarboxylic acid or its esterified product, 1,4-cyclohexanedimethanol and two aliphatic diols, respectively carrying out esterification reaction under the catalysis of an esterification catalyst to obtain a polyester oligomer, and then mixing the copolyester oligomer with a specific polycondensation catalyst to carry out a melt polycondensation reaction at 230° C. to 270° C., so that the obtained high-crystalline copolyester has not only good crystallization performance and high crystallinity, but also excellent thermal stability, mechanical properties and gas barrier properties.
[0085] In addition, the preparation method adopts an esterification-polycondensation process for preparation, wherein the esterification product can undergo polycondensation reaction without purification. Therefore, the preparation method is simple, convenient to operate, highly controllable, easy to implement, and suitable for large-scale industrial production.
[0086] As another aspect of the technical solution of the present invention, it also relates to the application of the aforementioned high-crystalline copolyester based on furandicarboxylic acid, specifically in the fields of preparing packaging materials, heat-resistant materials, agricultural mulch films, cling films or food tableware.
[0087] Furthermore, the packaging material may be express packaging material or food packaging material, etc., but is not limited thereto.
[0088] As another aspect of the technical solution of the present invention, it also relates to a high-crystalline copolyester product, which is prepared from the above-mentioned high-crystalline copolyester based on furandicarboxylic acid.
[0089] Furthermore, the high-crystalline copolyester product is processed by molding, injection molding, blow molding and other processing methods to obtain a high-melting-point fast-crystalline polyester product, which is mainly used in packaging film materials and heat-resistant container materials.
[0090] In summary, the highly crystalline copolyester of the present invention not only has excellent crystallization properties, high crystallinity and excellent thermodynamic properties, but also has excellent gas barrier properties. It fully illustrates the influence of different contents of high trans-content 1,4-cyclohexanedimethanol on various properties of highly crystalline copolyesters, constructs a structure-performance relationship, and provides very important guidance for the subsequent industrial copolyester synthesis. The highly crystalline copolyester can meet the requirements of use in a variety of temperatures and scenarios, and will not release various toxic and harmful substances during use. Therefore, it can be widely used in high temperature resistant materials, agricultural mulch films, cling films, express packaging, food packaging, and food tableware, effectively solving problems such as plastics being heat-resistant and gas barrier properties being too poor, and realizing the effective utilization of highly crystalline materials.
[0091] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0092] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0093] Hereinafter, the highly crystalline copolyester and its preparation method and product will be further described through the following specific examples.
[0094] In the embodiment, H NMR 1 H-NMR was measured on a Bruker 400AVANCE III Spectrometer at 400 MHz using deuterated trifluoroacetic acid (TFA) as the solvent.
[0095] In the examples, gel permeation chromatography (GPC) (Agilent PL-GPC220) was performed at 40°C using HPLC grade chloroform as the eluent at a flow rate of 1.0 mL min -1 According to the polystyrene standard, the 5 g mol -1 Molecular weight was calibrated within the range.
[0096] In the embodiment, the acid value is measured by volumetric titration. The sample is dissolved in a phenol-chloroform mixed solvent (volume ratio 2:3) by reflux, cooled, and titrated with bromophenol blue as an indicator using a potassium oxide-ethanol standard titration solution (c(KOH)=0.05mol / L). The content of the terminal carboxyl group is calculated based on the volume consumed by the standard titration solution.
[0097] In the embodiment, the hydroxyl value is measured by volumetric titration. The sample is dissolved in the acetylated mixed solution by reflux, and phenolphthalein is used as an indicator while hot. 1 mol / L sodium hydroxide standard solution is used for titration. The hydroxyl content is calculated based on the volume consumed by the standard titration solution.
[0098] In the examples, thermal analysis was performed using differential scanning calorimetry (Mettler Toledo DSC) at a heating rate of 10°C / min in a N2 atmosphere in the temperature range of -20°C to 280°C.
[0099] In the examples, thermogravimetric analysis (TGA) was performed on a Perkin-Elmer Diamond TG / DTA at a heating rate of 10°C / min in a temperature range of 50-800°C.
[0100] In the examples, the water contact angle (CA) is measured at room temperature and normal pressure using a WCA analyzer OCA20 (Dataphysics Ltd., Germany).
[0101] In the embodiment, the mechanical property test was conducted using an Instron 5567 universal material testing machine, with the sample strip dimensions of 35.0 mm in length, 2.0 mm in width, and 1.0 mm in thickness, and a tensile speed of 20 mm / min.
[0102] In the embodiment, Labthink VAC-V2 was used to test the barrier performance of O2 and CO2, wherein O2 and CO2 were used as gas sources, respectively, and the measurement was carried out under the conditions of temperature of 23°C and humidity of 50% RH. The sample size was Φ=97mm and the permeation area was 38.5cm 2 .
[0103] Example 1
[0104] The conventional two-step polycondensation method is used to prepare 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,6-hexanediol copolyester. 2,5-furandicarboxylic acid or its esterification product and 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,6-hexanediol are added to a three-necked flask in a certain ratio. The molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,6-hexanediol):2,5-furandicarboxylic acid is fixed at 1.5:1 (the excess glycol is ethylene glycol, and the excess 0.5 mol of ethylene glycol will be continuously extracted during the entire polycondensation process to promote the reaction. Finally, the alcohol-acid ratio in the polyester system will be close to 1:1). All reactions are carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.240 mol of 1,4-cyclohexanedimethanol, 0.195 mol of ethylene glycol and 0.015 mol of 1,6-hexanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 170°C. After reacting for 6 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0105] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 7:3), and then 0.1g of triphenyl phosphate and 0.1g of antioxidant 1010 were added, and the temperature was gradually raised to 260°C. A low vacuum degree was maintained for the reaction for 0.5h, and then the vacuum was gradually reduced to 7Pa for the reaction for 7h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-2):
[0106]
[0107] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0108] The NMR of the highly crystalline copolyester obtained in this example 1 H-NMR spectrum Figure 1 As shown, the DSC secondary heating curve is as follows Figure 2 The stress-strain curve is shown in Figure 3 The relative crystallinity and crystallization time are shown in Figure 4 As shown, the GPC curve is Figure 5 As shown, TGA Figure 6 shown.
[0109] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 79.5%, EG accounted for 15.5%, and 1,6-hexanediol accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 82.30℃, the crystallization temperature was 180.19℃, the melting temperature was 241.65℃, and the temperature at which the maximum decomposition rate was T d,max It is 410℃.
[0110] According to other tests, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 1.185 dL / g, a number average molecular weight of 43491 g / mol, a molecular weight distribution of 1.7, an acid value of 20 mol / t, a hydroxyl value of 30 KOHmg / g, an elastic modulus of 1512 MPa, a tensile strength of 59.88 MPa, an elongation at break of 132.7%, and a water contact angle of 87°. The CO2 permeability is 0.0393 barrer, and the CO2 barrier performance is 7.69 times that of PET; the O2 permeability is 0.0114 barrer, and the O2 barrier performance is 5.26 times that of PET. At 180°C, the half-crystallization time is 18.00s; at 190°C, the half-crystallization time is 29.15s.
[0111] Example 2
[0112] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,6-hexanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,6-hexanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,6-hexanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.270 mol of 1,4-cyclohexanedimethanol, 0.165 mol of ethylene glycol and 0.015 mol of 1,6-hexanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 220°C. After reacting for 4 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0113] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 6:4), and then 0.1g of triphenyl phosphate and 0.1g of antioxidant 1010 were added, and the temperature was gradually raised to 265°C. A relatively low vacuum degree was first maintained for 0.5h, and then the vacuum degree was gradually reduced to 7Pa. The reaction was continued for 5h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-3):
[0114]
[0115] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0116] After testing, the relative area of the nuclear magnetic resonance hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 89%, ethylene glycol accounted for 6%, and 16-hexanediol accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 83.0℃, the crystallization temperature was 184.2℃, the melting temperature was 245.7℃, and the temperature at which the maximum decomposition rate was T d , max It is 405℃.
[0117] According to other tests, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 1.300 dL / g, a number average molecular weight of 70,000 g / mol, a molecular weight distribution of 1.6, an acid value of 23 mol / t, a hydroxyl value of 33 OHmg / g, an elastic modulus of 1946 MPa, a tensile strength of 81.53 MPa, an elongation at break of 134.24%, and a water contact angle of 87°. The CO2 permeability is 0.0399 barrer, and the CO2 barrier performance is 3.25 times that of PET; the O2 permeability is 0.0126 barrer, and the O2 barrier performance is 4.76 times that of PET. At 160°C, the half-crystallization time is 69.3s; at 190°C, the half-crystallization time is 56.2s.
[0118] Example 3
[0119] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,8-octanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,8-octanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,6-octanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.210 mol of 1,4-cyclohexanedimethanol, 0.210 mol of ethylene glycol and 0.030 mol of 1,8-octanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 210°C. After reacting for 6 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0120] Then, isopropyl titanate and antimony acetate were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of isopropyl titanate to antimony acetate was 5:5), and then 0.1g of diphenyl phosphate and 0.1g of 2,6-di-tert-butyl-4-methylphenol were added, and the temperature was gradually raised to 255°C. A relatively low vacuum degree was maintained for reaction for 0.5h, and then the vacuum degree was gradually reduced to 7Pa for reaction for 8h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-4):
[0121]
[0122] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0123] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 68.5%, ethylene glycol accounted for 21.5%, and 1,8-octanediol accounted for 10%. From the DSC curve, the glass transition temperature of the copolyester was 82.20℃, the crystallization temperature was 176.19℃, the melting temperature was 235.65℃, and the temperature at which the maximum decomposition rate was T d , max It is 408℃.
[0124] After testing, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 0.8685 dL / g, a number average molecular weight of 43491 g / mol, a molecular weight distribution of 2.0, an acid value of 40 mol / t, a hydroxyl value of 39 KOHmg / g, an elastic modulus of 1703 MPa, a tensile strength of 43.32 MPa, an elongation at break of 125.52%, and a water contact angle of 87°. The CO2 permeability is 0.0241 barrer, and the CO2 barrier performance is 5.394 times that of PET; the O2 permeability is 0.0155 barrer, and the O2 barrier performance is 3.871 times that of PET. At 180°C, the half-crystallization time is 90.00s; at 190°C, the half-crystallization time is 73.26s.
[0125] Example 4
[0126] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,8-octanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its esterification product and 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,8-octanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,8-octanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.240 mol of 1,4-cyclohexanedimethanol, 0.189 mol of ethylene glycol and 0.021 mol of 1,8-octanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 215°C. After reacting for 5 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0127] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 9:1), and then triphenyl phosphate (accounting for 1.53‰ of the total molar amount of all acid raw materials) and antioxidant 1010 (accounting for 0.42‰ of the total molar amount of all acid raw materials) were added, and the temperature was gradually raised to 255°C, and a low vacuum degree was first maintained for 0.5h, and then the vacuum degree was gradually reduced to 7Pa, and the reaction was carried out for 10h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-5):
[0128]
[0129] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0130] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 79.5%, ethylene glycol accounted for 15.5%, and 1,8-octanediol accounted for 7%. From the DSC curve, the glass transition temperature of the copolyester was 83.50℃, the crystallization temperature was 179.19℃, the melting temperature was 239.65℃, and the temperature at which the maximum decomposition rate was T d,max It is 406℃.
[0131] After testing, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 0.8416 dL / g, a number average molecular weight of 43189 g / mol, a molecular weight distribution of 1.6, an acid value of 20 mol / t, a hydroxyl value of 38 OHmg / g, an elastic modulus of 1634 MPa, a tensile strength of 55.39 MPa, an elongation at break of 127.23%, and a water contact angle of 89°. The CO2 permeability is 0.0399 barrer, and the CO2 barrier performance is 3.25 times that of PET; the O2 permeability is 0.0126 barrer, and the O2 barrier performance is 4.76 times that of PET. At 180°C, the semi-crystallization time is 75.38 s; at 190°C, the semi-crystallization time is 64.26 s.
[0132] Example 5
[0133] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,10-decanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its esterification product and 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,8-octanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,10-decanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.210 mol of 1,4-cyclohexanedimethanol, 0.225 mol of ethylene glycol and 0.015 mol of 1,10-decanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 215°C. After reacting for 6 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0134] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 7:3), and then triphenyl phosphate (accounting for 1.53‰ of the total molar amount of all acid raw materials) and antioxidant 1010 (accounting for 0.42‰ of the total molar amount of all acid raw materials) were added, and the temperature was gradually raised to 255°C, and a low vacuum degree was first maintained for 0.5h, and then the vacuum degree was gradually reduced to 7Pa, and the reaction was carried out for 8h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar, and finally nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-6):
[0135]
[0136] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0137] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 69.5%, ethylene glycol accounted for 25.5%, and 1,10-decanediol accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 82.40℃, the crystallization temperature was 178.45℃, the melting temperature was 234.65℃, and the temperature at which the maximum decomposition rate was T d,max It is 404℃.
[0138] After testing, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 0.9205 dL / g, a number average molecular weight of 47688 g / mol, a molecular weight distribution of 1.6, an acid value of 22 mol / t, a hydroxyl value of 32 OHmg / g, an elastic modulus of 1654 MPa, a tensile strength of 64.23 MPa, and an elongation at break of 134.21%. The CO2 permeability is 0.0393 barrer, and the CO2 barrier performance is 3.30 times that of PET; the O2 permeability is 0.0107 barrer, and the O2 barrier performance is 5.6 times that of PET. At 180°C, the half crystallization time is 57.37s; at 190°C, the half crystallization time is 53.87s.
[0139] Example 6
[0140] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,10-decanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 76%, ethylene glycol and 1,8-octanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,10-decanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.270 mol of 1,4-cyclohexanedimethanol, 0.165 mol of ethylene glycol and 0.015 mol of 1,10-decanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 220°C. After reacting for 5 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0141] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 7:3), and then triphenyl phosphate (accounting for 1.53‰ of the total molar amount of all acid raw materials) and antioxidant 1010 (accounting for 0.42‰ of the total molar amount of all acid raw materials) were added, and the temperature was gradually raised to 270°C, and a relatively low vacuum degree was maintained for reaction for 0.5h, and then the vacuum degree was gradually reduced to 7Pa, and the reaction was carried out for 7h until the torque of the stirrer reached a fixed value to ensure that the viscosity of all products was similar, and finally nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester, whose structural formula is shown in formula (1-7):
[0142]
[0143] x, y, z, and n are all integers, x=1-10, y=1-10, z=1-10, n=20-100; wherein, (x+z):y=1:1-1:10.
[0144] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 90%, ethylene glycol accounted for 5%, and 1,10-decanediol accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 87.00℃, the crystallization temperature was 192.45℃, the melting temperature was 249.65℃, and the temperature at which the maximum decomposition rate was T d,max It is 412℃.
[0145] After testing, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 0.700 dL / g, a number average molecular weight of 30,000 g / mol, a molecular weight distribution of 2.0, an acid value of 36 mol / t, a hydroxyl value of 50 KOHmg / g, an elastic modulus of 1723 MPa, a tensile strength of 43.54 MPa, an elongation at break of 24.21%, and a water contact angle of 87°. The CO2 permeability is 0.0592 barrer, and the CO2 barrier performance is 2.45 times that of PET; the O2 permeability is 0.0271 barrer, and the O2 barrier performance is 2.21 times that of PET. At 190°C, the half-crystallization time is 63.29s; at 200°C, the half-crystallization time is 58.28s.
[0146] Example 7
[0147] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,12-dihydroxydodecane copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,12-dihydroxydodecane were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,12-dihydroxydodecane):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask, and the flask was equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.180 mol of 1,4-cyclohexanedimethanol, 0.255 mol of ethylene glycol and 0.015 mol of 1,12-dihydroxydodecane were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 210°C. After reacting for 5 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0148] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 7:3), and then triphenyl phosphate (accounting for 1.53‰ of the total molar amount of all acid raw materials) and antioxidant 1010 (accounting for 0.42‰ of the total molar amount of all acid raw materials) were added, and the temperature was gradually raised to 250°C. A relatively low vacuum degree was maintained for the reaction for 0.5h, and then the vacuum degree was gradually reduced to 7Pa for the reaction for 8h until the torque of the agitator reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester.
[0149] After testing, the relative area of the nuclear magnetic resonance hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 58.5%, ethylene glycol accounted for 36.5%, and 1,12-dihydroxydodecane accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 76.00℃, the crystallization temperature was 178.45℃, the melting temperature was 229.75℃, and the temperature at which the maximum decomposition rate was T d,max It is 405℃.
[0150] According to other tests, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 1.165 dL / g, a number average molecular weight of 53491 g / mol, a molecular weight distribution of 1.7, an acid value of 26 mol / t, a hydroxyl value of 37 KOHmg / g, an elastic modulus of 1412 MPa, a tensile strength of 79.88 MPa, an elongation at break of 152.7%, and a water contact angle of 89°. The CO2 permeability is 0.0467 barrer, and the CO2 barrier performance is 6.47 times that of PET; the O2 permeability is 0.0324 barrer, and the O2 barrier performance is 1.85 times that of PET. At 180°C, the half-crystallization time is 35.00s; at 190°C, the half-crystallization time is 33.05s.
[0151] Example 8
[0152] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,12-dihydroxydodecane copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 75%, ethylene glycol and 1,12-dihydroxydodecane were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,12-dihydroxydodecane):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask, and the flask was equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.210 mol of 1,4-cyclohexanedimethanol, 0.210 mol of ethylene glycol and 0.030 mol of 1,12-dihydroxydodecane were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was raised to 215°C. After reacting for 5 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0153] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 5:5), and then triphenyl phosphate (accounting for 1.53‰ of the total molar amount of all acid raw materials) and antioxidant 1010 (accounting for 0.42‰ of the total molar amount of all acid raw materials) were added, and the temperature was gradually raised to 250°C. A relatively low vacuum degree was maintained for the reaction for 0.5h, and then the vacuum degree was gradually reduced to 7Pa for the reaction for 8h until the torque of the agitator reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester.
[0154] After testing, the relative area of the nuclear magnetic resonance hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 69.5%, ethylene glycol accounted for 20.5%, and 1,12-dihydroxydodecane accounted for 10%. From the DSC curve, the glass transition temperature of the copolyester was 79.20℃, the crystallization temperature was 181.45℃, the melting temperature was 232.75℃, and the temperature at which the maximum decomposition rate was T d,max It is 403℃.
[0155] According to other tests, the high crystalline copolyester prepared in this embodiment has an intrinsic viscosity of 1.075 dL / g, a number average molecular weight of 41491 g / mol, a molecular weight distribution of 1.6, an acid value of 36 mol / t, a hydroxyl value of 34 KOHmg / g, an elastic modulus of 1465 MPa, a tensile strength of 66.88 MPa, an elongation at break of 156.7%, and a water contact angle of 89°. The CO2 permeability is 0.0496 barrer, and the CO2 barrier performance is 6.10 times that of PET; the O2 permeability is 0.0363 barrer, and the O2 barrier performance is 1.65 times that of PET. At 180°C, the half-crystallization time is 38.00 s; at 190°C, the half-crystallization time is 39.75 s.
[0156] Example 9
[0157] Compared with Example 2, this embodiment is different in that ethylene glycol is replaced by neopentyl glycol, the esterification catalyst accounts for 3‰ of the total molar amount of all acid raw materials, the polycondensation catalyst accounts for 3‰ of the total molar amount of all acid raw materials, the triphenyl phosphate accounts for 3‰ of the total molar amount of all acid raw materials, and the antioxidant accounts for 0.5‰ of the total molar amount of all acid raw materials.
[0158] After testing, the relative area of the nuclear magnetic resonance hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 90%, neopentyl glycol accounted for 5%, and 16-hexanediol accounted for 5%. From the DSC curve, the glass transition temperature of the copolyester was 82.2℃, the crystallization temperature was 180.3℃, the melting temperature was 242.1℃, and the temperature at which the maximum decomposition rate was T d,maxIt is 404℃.
[0159] According to other tests, the intrinsic viscosity of the high crystalline copolyester prepared in this embodiment is 1.211dL / g, the number average molecular weight is 64200g / mol, the molecular weight distribution is 1.7, the acid value is 28mol / t, the hydroxyl value is 37OHmg / g, the elastic modulus is 1990MPa, the tensile strength is 86.23MPa, the elongation at break is 138.24%, and the water contact angle of the film is 88°. At 160°C, the half crystallization time is 67.2s; at 190°C, the half crystallization time is 54.9s.
[0160] Example 10
[0161] Compared with Example 7, this embodiment is different in that ethylene glycol is replaced by 1,2-pentanediol. The esterification catalyst accounts for 1‰ of the total molar amount of all acid raw materials, the polycondensation catalyst accounts for 1‰ of the total molar amount of all acid raw materials, the triphenyl phosphate accounts for 1‰ of the total molar amount of all acid raw materials, and the antioxidant accounts for 0.4‰ of the total molar amount of all acid raw materials.
[0162] After testing, the relative area of the nuclear magnetic resonance hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 59.5%, 1,2-pentanediol was 35.5%, and 1,12-dihydroxydodecane was 5%. From the DSC curve, the glass transition temperature of the copolyester was 78.2℃, the crystallization temperature was 179.8℃, the melting temperature was 230.3℃, and the temperature at which the maximum decomposition rate was T d,max It is 406℃.
[0163] According to other tests, the intrinsic viscosity of the high crystalline copolyester prepared in this embodiment is 1.021dL / g, the number average molecular weight is 48491g / mol, the molecular weight distribution is 1.6, the acid value is 29mol / t, the hydroxyl value is 39KOHmg / g, the elastic modulus is 1425MPa, the tensile strength is 79.92MPa, the elongation at break is 127.7%, and the water contact angle of the film is 88°. At 180°C, the half crystallization time is 29.00s; at 190°C, the half crystallization time is 30.2s.
[0164] Embodiment 11
[0165] Compared with Example 8, this embodiment is different in that ethylene glycol is replaced by diethylene glycol, the esterification catalyst accounts for 2‰ of the total molar amount of all acid raw materials, triphenyl phosphate accounts for 5‰ of the total molar amount of all acid raw materials, and the antioxidant accounts for 0.6‰ of the total molar amount of all acid raw materials.
[0166] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 70%, diethylene glycol accounted for 20%, and 1,12-dihydroxydodecane accounted for 10%. From the DSC curve, the glass transition temperature of the copolyester was 80.20℃, the crystallization temperature was 182.20℃, the melting temperature was 233.9℃, and the temperature at which the maximum decomposition rate was T d,max It is 405℃.
[0167] According to other tests, the intrinsic viscosity of the high crystalline copolyester prepared in this embodiment is 1.121dL / g, the number average molecular weight is 42937g / mol, the molecular weight distribution is 1.6, the acid value is 37mol / t, the hydroxyl value is 39KOHmg / g, the elastic modulus is 1489MPa, the tensile strength is 86.86MPa, the elongation at break is 159.7%, and the water contact angle of the film is 88°. At 180°C, the half crystallization time is 31.7s; at 190°C, the half crystallization time is 36.8s.
[0168] Example 12
[0169] Compared with Example 8, this embodiment is different in that ethylene glycol is replaced by 1,5-pentanediol, the esterification catalyst accounts for 1.85‰ of the total molar amount of all acid raw materials, triphenyl phosphate accounts for 4.8‰ of the total molar amount of all acid raw materials, and the antioxidant accounts for 0.58‰ of the total molar amount of all acid raw materials.
[0170] After testing, the relative area of the nuclear magnetic hydrogen spectrum peak was calculated, and the proportion of 1,4-cyclohexanedimethanol in the highly crystalline copolyester was 75%, 1,5-pentanediol was 17%, and 1,12-dihydroxydodecane was 8%. From the DSC curve, the glass transition temperature of the copolyester was 85.60℃, the crystallization temperature was 198.3℃, the melting temperature was 238.7℃, and the temperature at which the maximum decomposition rate was T d,max It is 407℃.
[0171] According to other tests, the intrinsic viscosity of the high crystalline copolyester prepared in this embodiment is 1.20 dL / g, the number average molecular weight is 44578 g / mol, the molecular weight distribution is 1.6, the acid value is 28 mol / t, the hydroxyl value is 35 KOHmg / g, the elastic modulus is 1877 MPa, the tensile strength is 78.65 MPa, the elongation at break is 108.7%, and the water contact angle of the film is 85°. At 180°C, the half crystallization time is 27.7s; at 190°C, the half crystallization time is 19.8s.
[0172] Comparative Example 1
[0173] PCF-trans68 copolyester was prepared by conventional two-step polycondensation method. 2,5-furandicarboxylic acid or its ester and 1,4-cyclohexanedimethanol with trans content of 68% were added to a three-necked flask in a certain ratio. The molar ratio of 1,4-cyclohexanedimethanol:2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 250ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30mol of dimethyl 2,5-furandicarboxylate and 0.45mol of 1,4-cyclohexanedimethanol were added to the flask, and then esterification catalyst zinc acetate (accounting for 2.0‰ of all acid moles) was added. Under vacuum (0.1kpa), it was purged with nitrogen three times, and then reacted at 200℃ constant nitrogen environment for 4h to obtain polyester oligomer.
[0174] A second catalyst, antimony trioxide (1.5‰ of all acid moles), was added to the polyester oligomer, and then the temperature was raised to 240°C. The pressure of the reaction system was gradually reduced to 10 Pa for a period of time until the torque of the agitator reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain the target product.
[0175] After testing, the PCF-trans68 prepared in this comparative example has an intrinsic viscosity of 0.60dL / g, a number average molecular weight of 23000g / mol, a molecular weight distribution of 1.80, an acid value of 38mol / t, a hydroxyl value of 46K0Hmg / g, a tensile strength of 32MPa, an elongation at break of 78%, and a semi-crystallization time of 92s at 160°C; and a semi-crystallization time of 88s at 170°C.
[0176] Compared with Example 1, the present comparative example does not add the two copolymerized diols, which results in difficulty in removing cyclohexanedimethanol during the polycondensation process, difficulty in the forward reaction, and a low molecular weight of the final product; at the same time, no long-chain diol is added to improve flexibility, resulting in poor mechanical properties of the copolyester, weakened crystallization properties, and varying degrees of weakening of the gas barrier properties. At the same temperature, the half-crystallization time increases by nearly 50s, and the crystallization properties also decrease.
[0177] Comparative Example 2
[0178] PECTF copolyester was prepared by conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 41% and 2,2,4,4-tetramethyl-1,3-cyclobutanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol + 2,2,4,4-tetramethyl-1,3-cyclobutanediol): 2,5-furandicarboxylic acid was fixed at 1.5: 1. All reactions were carried out in a 250 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.26 mol of 1,4-cyclohexanedimethanol and 0.19 mol of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (CBDO) were added into a flask, and then the esterification catalyst zinc acetate (accounting for 2.0‰ of all acid moles) was added, and the mixture was purged with nitrogen three times under vacuum (0.1 kPa), and then reacted at 220°C in a constant nitrogen environment for 3 hours to obtain a polyester oligomer.
[0179] A second catalyst, antimony trioxide (1.5‰ of all acid moles) is added to the polyester oligomer, and then the temperature is raised to 260°C. The pressure of the reaction system is gradually reduced to 10-30 Pa for a period of time until the torque of the agitator reaches a fixed value to ensure that the viscosity of all products is similar. Finally, nitrogen is introduced to restore the reaction pressure to normal pressure to obtain the target product.
[0180] After testing, the intrinsic viscosity of PECTF prepared in this comparative example is 0.762dL / g, the number average molecular weight is 23400g / mol, the molecular weight distribution is 1.70, the acid value is 38mol / t, the hydroxyl value is 48KOHmg / g, the glass transition temperature is 77°C, the tensile strength is 12MPa, and the elongation at break is 19%. At 150°C, the half crystallization time is 99.28s; at 170°C, the half crystallization time is 93.56s.
[0181] Compared with Example 1, due to the lack of high-content high-trans 1,4-cyclohexanedimethanol, the molecular chain regularity of this comparative example deteriorates, the molecular weight is difficult to increase, the crystallization ability deteriorates, the half-crystallization time is significantly increased, and various mechanical properties and barrier properties also decrease to varying degrees.
[0182] Comparative Example 3
[0183] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-1,8-octanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78% and 1,8-octanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol + 1,6-octanediol): 2,5-furandicarboxylic acid was fixed at 1.5: 1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.210 mol of 1,4-cyclohexanedimethanol and 0.240 mol of 1,8-octanediol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was slowly raised from 170°C to 210°C. After reacting for 3 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0184] Then, isopropyl titanate and antimony acetate are added as condensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of isopropyl titanate to antimony acetate is 7:3), and then 0.1g of diphenyl phosphate and 0.1g of 2,6-di-tert-butyl-4-methylphenol are added, and the temperature is gradually raised to 255°C. A relatively low vacuum degree is maintained for a period of time, and then the vacuum degree is gradually reduced to 7Pa, and the reaction is carried out for 2-8h until the torque of the agitator reaches a fixed value to ensure that the viscosity of all products is similar. Finally, nitrogen is introduced to restore the reaction pressure to normal pressure to obtain a highly crystalline copolyester.
[0185] After testing, the intrinsic viscosity of the product prepared in this comparative example is 0.656dL / g, the number average molecular weight is 26490g / mol, the molecular weight distribution is 1.90, the acid value is 42mol / t, the hydroxyl value is 49KOHmg / g, the tensile strength is 25MPa, and the elongation at break is 16%. At 150°C, the half crystallization time is 99.28s; at 170°C, the half crystallization time is 93.56s.
[0186] Compared with Example 3, due to the lack of the second diol ethylene glycol, the reaction in this comparative example is difficult to proceed forward during the polycondensation process, and the molecular weight increases slowly, thereby obtaining a copolyester with a shorter molecular chain and a larger dispersion coefficient. It is difficult to increase the molecular weight, and various mechanical properties and barrier properties also decrease to varying degrees.
[0187] Comparative Example 4
[0188] Preparation by conventional two-step polycondensation method 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol copolyester was prepared by conventional two-step polycondensation method. 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78% and ethylene glycol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol + ethylene glycol): 2,5-furandicarboxylic acid was fixed at 1.5: 1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.240 mol of 1,4-cyclohexanedimethanol and 0.210 mol of ethylene glycol were added into a three-necked flask, and then 0.065 g of tetrabutyl titanate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was slowly raised from 170°C to 210°C. After reacting for 4 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0189] Then, tetrabutyl titanate and antimony trioxide were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of antimony trioxide to tetrabutyl titanate was 7:3), and then 0.1g of triphenyl phosphate and 0.1g of antioxidant 1010 were added, and the temperature was gradually raised to 260°C. A low vacuum degree was maintained for the reaction for 0.5h, and then the vacuum was gradually reduced to 10Pa, and the reaction was carried out for 7h until the torque of the agitator reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol copolyester.
[0190] After testing, it was calculated from the relative area of the nuclear magnetic hydrogen spectrum peak that in the 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol copolyester, 1,4-cyclohexanedimethanol accounted for 79.5% and ethylene glycol accounted for 20.5%. The glass transition temperature of the copolyester is 82.20℃, the crystallization temperature is 178.4℃, and the melting temperature is 238.5℃. According to other tests, the copolyester has an intrinsic viscosity of 1.145dL / g, a number average molecular weight of 39491g / mol, a molecular weight distribution of 1.9, an acid value of 33mol / t, a hydroxyl value of 38KOHmg / g, a tensile strength of 27.67MPa, and an elongation at break of 24.2%; at 180℃, the semi-crystallization time is 38.00s; at 190℃, the semi-crystallization time is 59.46s.
[0191] Compared with Example 1, this comparative example lacks the second diol 1,6-hexanediol. The obtained PECF has higher thermal performance due to the presence of high trans-content CHDM, but lacks the addition of tough chains, which makes it have a high rigidity as a whole, resulting in a significant decrease in mechanical properties and poor crystallization ability. At the same temperature, the crystallization time is nearly twice as long as that of the long-chain diol.
[0192] Comparative Example 5
[0193] 2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol-1,6-hexanediol copolyester was prepared by a conventional two-step polycondensation method, 2,5-furandicarboxylic acid or its ester, 1,4-cyclohexanedimethanol with a trans content of 78%, ethylene glycol and 1,6-hexanediol were added to a three-necked flask in a certain ratio, and the molar ratio of (1,4-cyclohexanedimethanol+ethylene glycol+1,6-hexanediol):2,5-furandicarboxylic acid was fixed at 1.5:1. All reactions were carried out in a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer with a torque indicator. 0.30 mol of dimethyl 2,5-furandicarboxylate, 0.240 mol of 1,4-cyclohexanedimethanol, 0.195 mol of ethylene glycol and 0.015 mol of 1,6-hexanediol were added into a three-necked flask, and then 0.065 g of tin 2-ethylhexanoate was added. Under vacuum (0.1 kPa), the mixture was purged with nitrogen three times, and then the temperature was slowly raised from 180°C to 200°C. After reacting for 4 hours under a constant nitrogen environment, a polyester oligomer was obtained.
[0194] Then, KHCO3 and Ca(Ac)2 were added as polycondensation catalysts (accounting for 1.50‰ of the total molar amount of all acid raw materials, wherein the molar ratio of KHCO3 to Ca(Ac)2 was 7:3), and then 0.1g of triphenyl phosphate and 0.1g of antioxidant 1010 were added. The temperature was gradually increased to 250°C, and the vacuum degree was gradually reduced to 10Pa. The reaction was carried out for more than 5h until the torque of the agitator reached a fixed value to ensure that the viscosity of all products was similar. Finally, nitrogen was introduced to restore the reaction pressure to normal pressure to obtain the target product.
[0195] After testing, the high crystalline copolyester prepared in this comparative example has an intrinsic viscosity of 0.4544 dL / g, a number average molecular weight of 18568 g / mol, a molecular weight distribution of 2.0, an acid value of 55 mol / t, a hydroxyl value of 63 KOHmg / g, an elastic modulus of 1232 MPa, a tensile strength of 33.32 MPa, and an elongation at break of 22.33%. At 180°C, the half crystallization time is 93.30 s; at 190°C, the half crystallization time is 92.16 s.
[0196] Compared with Example 1, this comparative example uses the same monomers and experimental steps, but uses a conventional catalyst. The molecular weight of the copolyester obtained is the lowest. The reason for this is that the conventional catalyst has poor thermal stability and low activity with the reaction monomers, which leads to the generation of side reactions and slow reaction speed. The reaction time is too long, the color of the copolyester tends to be dark yellow, and the crystallization ability is poor.
[0197] It can be seen from the examples and comparative examples that the highly crystalline copolyester prepared in the present invention not only has excellent crystallization properties and thermodynamic properties, but also has good mechanical properties and gas barrier properties.
[0198] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0199] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A highly crystalline copolyester based on furandicarboxylic acid, characterized in that: The structural formula of the highly crystalline copolyester is shown in the following formula (1): Wherein, R1 is -O(CH2) a O-, R2 is -O(CH2) b O-, a, b, x, y, z, n are all integers, a=2~6, b=6~12, x=1~10, y=1~10, z=1~10, n=20~100; and, (x+z):y=1:1N1:
10.
2. The highly crystalline copolyester based on furandicarboxylic acid according to claim 1, characterized in that: The glass transition temperature of the highly crystalline copolyester is 76 to 87° C., the melting temperature is 230 to 270° C., and the half-crystallization time of the highly crystalline copolyester during isothermal crystallization at 160 to 200° C. is 18 to 90 seconds; And / or, the high crystalline copolyester has an intrinsic viscosity of 0.7 dL / g to 1.3 dL / g, a number average molecular weight of 30,000 g / mol to 70,000 g / mol, a molecular weight distribution of 1.6 to 2.0, an acid value of 20 to 40 mol / t, and a hydroxyl value of 30 to 50 mgKOH / g.
3. A highly crystalline copolyester based on furandicarboxylic acid, characterized in that: It is prepared from raw materials including the following components: 2,5-Furandicarboxylic acid and / or 2,5-furandicarboxylic acid esters; A 1,4-cyclohexanedimethanol composition, comprising trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%; A first aliphatic diol having 2 to 6 carbon atoms; The second aliphatic diol having 6 to 12 carbon atoms.
4. The highly crystalline copolyester based on furandicarboxylic acid according to claim 3, characterized in that: In a mixture of a 1,4-cyclohexanedimethanol composition, a first aliphatic diol, and a second aliphatic diol, the molar content of the 1,4-cyclohexanedimethanol composition is 60 to 90%; and / or, in a mixture of the 1,4-cyclohexanedimethanol composition, the first aliphatic diol, and the second aliphatic diol, the molar content of the first aliphatic diol is 5 to 35%, and the molar content of the second aliphatic diol is 5 to 10%; and / or, the molar ratio of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, 1,4-cyclohexanedimethanol composition, the first aliphatic diol and the second aliphatic diol is 1:0.6:0.35:0.05 to 1:0.9:0.05:0.05; And / or, the first aliphatic diol includes any one or a combination of two or more of ethylene glycol, 1,2-pentanediol, 1,4-pentanediol, 1,5-pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, diethylene glycol, and 1,6-hexanediol; And / or, the second aliphatic diol includes any one of 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dihydroxydodecane, or a combination of two or more thereof.
5. The highly crystalline copolyester based on furandicarboxylic acid according to claim 4, characterized in that: The first aliphatic diol is ethylene glycol; and / or the second aliphatic diol is octanediol.
6. A method for preparing a highly crystalline copolyester based on furandicarboxylic acid, characterized in that: include: Conducting an esterification reaction or an esterification reaction on a first mixed reaction system comprising 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, a 1,4-cyclohexanedimethanol composition, a first aliphatic diol having 2 to 6 carbon atoms, a second aliphatic diol having 6 to 12 carbon atoms, and an esterification catalyst to obtain a copolyester oligomer, wherein the 1,4-cyclohexanedimethanol composition comprises trans-1,4-cyclohexanedimethanol and cis-1,4-cyclohexanedimethanol, wherein the content of trans-1,4-cyclohexanedimethanol in the 1,4-cyclohexanedimethanol composition is 75% to 78%; Under vacuum conditions, a second mixed reaction system comprising the copolyester oligomer and a polycondensation catalyst is subjected to a melt polycondensation reaction to prepare a furandicarboxylic acid-based high-crystalline copolyester.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester, 1,4-cyclohexanedimethanol composition, the first aliphatic diol and the second aliphatic diol is 1:0.6:0.35:0.05 to 1:0.9:0.05:0.05; And / or, the first aliphatic diol includes any one or a combination of two or more of ethylene glycol, 1,2-pentanediol, 1,4-pentanediol, 1,5-pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, diethylene glycol, and 1,6-hexanediol; And / or, the second aliphatic diol includes any one of 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dihydroxydodecane, or a combination of two or more thereof.
8. The preparation method according to claim 7, characterized in that: The first aliphatic diol is ethylene glycol; and / or, the second aliphatic diol is octanediol; And / or, the preparation method comprises: subjecting the first mixed reaction system to an esterification reaction or an ester exchange reaction at 170 to 220° C. for 4 to 6 hours to obtain a first intermediate product; and / or, when the yield of by-product water or methanol reaches 95% or more, the esterification reaction or transesterification reaction in the first mixed reaction system is completed; And / or, the esterification catalyst includes any one or a combination of two or more of a titanium-based catalyst, an antimony-based catalyst, a tin-based catalyst, and a germanium-based catalyst; And / or, the molar amount of the esterification catalyst is 1‰ to 3‰ of the total molar amount of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid esters.
9. The preparation method according to claim 8, characterized in that: The esterification catalyst includes at least any one of tetrabutyl titanate, isopropyl titanate, and antimony acetate; And / or, the preparation method comprises: First, the second mixed reaction system is maintained in a low vacuum state, and then the vacuum degree is increased until the melt polycondensation reaction is stable, the vacuum degree is maintained below 7 Pa, and after the reaction is completed, the normal pressure is restored to obtain a high crystalline copolyester based on furandicarboxylic acid; And / or, the temperature of the melt polycondensation reaction is 250°C to 270°C, and the time of the melt polycondensation reaction is 5h to 10h; and / or, the molar amount of the polycondensation catalyst is 1‰ to 3‰ of the total molar amount of 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid esters; And / or, the polycondensation catalyst comprises a mixture of an antimony catalyst and a titanium catalyst, wherein the mass ratio of the antimony catalyst to the titanium catalyst is 5:5 to 9:1; the antimony catalyst comprises at least any one of antimony trioxide, antimony acetate, and antimony glycol; the titanium catalyst comprises at least any one of tetrabutyl titanate, titanium dioxide, and potassium hexafluorotitanate; And / or, the second mixed reaction system further comprises at least any one of a stabilizer and an antioxidant; the molar amount of the stabilizer is 1‰ to 5‰ of the total molar amount of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester; the stabilizer is selected from a phosphorus stabilizer, wherein the phosphorus stabilizer comprises at least any one of phosphorous acid, diphenyl phosphate, triphenyl phosphate, and triphenyl phosphite; The molar amount of the antioxidant is 0.4‰ to 0.6‰ of the total molar amount of the 2,5-furandicarboxylic acid and / or 2,5-furandicarboxylic acid ester; the antioxidant is selected from phenolic antioxidants, wherein the phenolic antioxidant includes at least any one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol, and 2,2-methylenebis(4-methyl-6-tert-butylphenol).
10. The preparation method according to claim 9, characterized in that: The polycondensation catalyst includes a mixture of antimony trioxide and tetrabutyl titanate; and / or the phosphorus stabilizer includes at least one of triphenyl phosphate and triphenyl phosphite; and / or the phenolic antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
11. Use of the high crystalline copolyester based on furandicarboxylic acid according to any one of claims 1 to 5 in the preparation of packaging materials, heat-resistant materials, agricultural mulch films, cling films or food tableware.
12. The use according to claim 11, characterized in that: The packaging material includes express packaging material or food packaging material.
13. A highly crystalline copolyester product, characterized in that: The highly crystalline copolyester product is prepared from the highly crystalline copolyester based on furandicarboxylic acid according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of low-yellowing 2,5-furandicarboxylic acid-based polyester
CN102516513A
Furan dicarboxylic acid copolyester and preparation method and application thereof
CN108129644A
Furan dicarboxylic acid copolyester and preparation method thereof
CN109721716A
Multi-block copolymer based on 2,5-furandicarboxylic acid polyester and aliphatic polycarbonate, and preparation method of multi-block copolymer
CN110407991A
Polyester with high heat resistance and high toughness, polyester product, and preparation method and application thereof
CN112592471A
Cited By
Crystalline low-melting-point polyester fiber and preparation method thereof
CN120797253A
Furandicarboxylic acid block copolyester and preparation method thereof
CN121554718A